River discharge to the coastal ocean : Global Synthesis - Milliman, John D. (Cambridge University Press, 2011)
"Rivers provide the primary link between land and sea. Utilizing the world's largest database, this book presents a detailed analysis and synthesis of the processes affecting fluvial discharge of water, sediment and dissolved solids. The ways in which climatic variation, episodic events, and anthropogenic activities - past, present and future - affect the quantity and quality of river discharge are discussed in the final two chapters. The book contains 26 tables and more than 165 figures - many in full color - including global and regional maps. The book's extensive appendix presents the 1534-river database as a series of 44 tables that provide quantitative data regarding the discharge of water, sediment and dissolved solids. The complete database is also presented within a GIS-based package available online at www.cambridge.org/milliman. River Discharge to the Coastal Ocean provides an invaluable resource for researchers, professionals and graduate students in hydrology, oceanography, geology, geomorphology and environmental policy"--